The Fetters of the Sib: An Experimental Study in Burkina Faso - Björn Vollan; Myriam Hadnes; Marco Nilgen; Michael Kosfeld (Institute of Labor Economics (IZA), 2021)
We conducted a field experiment in Burkina Faso to investigate the impact of sharing obligations within kin networks on entrepreneurial effort. The overall treatment effect we find is insignificant and goes in the opposite direction than previous literature suggests. Ex-post explorative analysis reveals that entrepreneurs in the two experimental groups reacted differently in their production process, with some entrepreneurs in the treatment group being able to utilize their kin network to their joint advantage.
Keywords: C93; D13; H24; H26; O12; 330; field experiment; redristributive pressure; social norms; sharing norms; business development; Burkina Faso